Osteoimmune Interaction and TH-1/TH-2 Ratio in Jawbone Marrow Defects: An Underestimated Association – Original Research - Lechner, Johann; von Baehr, Volker; Notter, Florian; Schick, Fabian (Biologics, 2024)
Osteoimmunology recognizes the relationship between bone cells and immune cells. Chronic osteoimmune dysregulation is present in bone marrow defects of the jaw (BMDJ) as fatty-degenerative osteonecrosis (FDOJ). In comparison to samples from healthy jaw bone, the cytokine analysis of samples of BMDJ/FDOJ from 128 patients showed downregulated TNF-α and IL-6 expression and the singular overexpression of the chemokine RANTES/CCL5. This paper raises the question of whether the osteoimmune defects due to incomplete wound healing in BMDJ/FDOJ in 128 patients are related to dysregulation of the Th1/Th2 ratio and regulatory T cell (T-reg) expression in a control group of 197 BMDJ/FDOJ patients, each presenting with BMDJ/FJOD and one of seven different immune disorders. In the control group, serum concentrations of the cytokines IFN-y and IL-4 were determined after stimulated cytokine release and displayed as Th1/Th2 ratios. Data show a shift in Th2 in more than 80% (n = 167) of the control cohort of 197 chronically ill patients with concomitant BMDJ/FDOJ. In these 167 subjects, the Th1/Th2 ratio was <6.1 demonstrating impaired immune regulation. Forty-seven subjects or 30% showed not only a shift in Th2 but also excessive T-reg overactivation with levels of >1.900 pg/mL, indicating strongly downregulated immune activity. BMDJ/FDOJ is characterized by a lack of Th1 cytokines and an excessive expression of RANTES/CCL5 and IL-1ra and, thus, the inversion of an acute inflammatory cytokine pattern. In contrast, abdominal fat contains a very high proportion of regulatory Th1 cells and produces an inflammatory immune response through the high overexpression of TNF-α and IL-6. The lack of Th1 activation in BMDJ/FDOJ areas inhibits normal wound healing and supports the persistence of BMDJ/FDOJ. The Th1/Th2 ratio requires greater consideration, especially with respect to wound healing following dental surgical interventions, such as jaw surgery, implantation and augmentation, to avoid the emergence of the osteoimmune situation that is characteristic of BMDJ/FDOJ.